Information Structure and Scope Interactions: Disjunction Wide Scope Induced by Focus - Larralde, Cécile; Konradt, Alina; Szendrői, Kriszta Eszter (Frontiers in Communication, 2021)
In this paper we investigate the scopal reading of disjunctions in French negative sentences with pre-schoolers. We posit that the French disjunctor “ou” does not fit the traditional disjunction PPI/non-PPI dichotomy according to which a wide scope is taken by a PPI disjunction and negation takes wide scope when the disjunction is not a PPI. We hypothesised that focus could be a succesful scopal manipulator. Us-ing the Truth Value Judgment Tasks (TVJT) of Goro et al (2004), we tested French pre-schoolers' scopal reading of negated disjunctions in a neutral prosody condition and with prosodic focus on the disjunctor in a between subject design. We found that as predicted, prosodic focus often enduced participants to adopt a disjunction wide scope reading whereas a negation wide scope reading was favored in the neutral prosody condition. This confirmed our hypothesis that focus can manipulate disjunction scope paramaters. It also shows that, when the disjunction is focalised, children have access to the disjunction wide scope reading earlier than previously thought. Finally, we can conclude that the distinction between PPI-disjunctor vs non-PPI disjunctor languages needs to be more fine-grained.